1962
DOI: 10.1149/1.2425538
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Electrochemical Kinetics of Indium

Abstract: The kinetics of the deposition and dissolution of indium (from indium amalgam) in indium sulfate solutions at pH 2.5 have been studied by observing variations of overpotential during individual constant current pulses. The electrode was in the form of a hanging drop of the amalgam, which was renewed for each pulse. The steady-state activation overpotential was reached approximately 1 msec after application of the pulse, which corresponds to a mean value of double layer capacity of 25.4 ~F/cm ~. Plots of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 6 publications
2
28
0
Order By: Relevance
“…To study the phenomenon, the cathodic and anodic polarization in solutions of indium sulfate with pH 2.5, 1.56 and 1.0 was investigated. On the basis of the shape of the the η A -log 10 i curve and their earlier considerations it followed, 42) that going from lower current densities to higher ones, a change in the mechanism of the deposition of indium occurred. They explained that one mechanism was predominant at lower current densities and the other at higher current densities, while in the region between both processes were possible.…”
Section: /Inmentioning
confidence: 92%
See 1 more Smart Citation
“…To study the phenomenon, the cathodic and anodic polarization in solutions of indium sulfate with pH 2.5, 1.56 and 1.0 was investigated. On the basis of the shape of the the η A -log 10 i curve and their earlier considerations it followed, 42) that going from lower current densities to higher ones, a change in the mechanism of the deposition of indium occurred. They explained that one mechanism was predominant at lower current densities and the other at higher current densities, while in the region between both processes were possible.…”
Section: /Inmentioning
confidence: 92%
“…In solutions of pH in the region <~2.7, an indium electrode behaved in a satisfactory manner but at pH's >~2.7, the potential changes markedly for small changes of pH. They explained that the electrode reaction, In 3+ + 3e ↔ In 42) studied the kinetics of the deposition and dissolution of indium (from indium amalgam) in indium sulfate solution at pH 2.5 by observing variations of overpotential during individual constant current pulses. For the electrochemical deposition and dissolution of indium in the region of lower current densities (< 2.5 × 10 −3 A cm −2 ) it was found that the mechanism consisted of three consecutive electron transfer steps:…”
Section: )mentioning
confidence: 99%
“…The catalytic effect of the anions on the kinetics of indium reduction increases in the order F ) <ClO ) 4 < SO 4 2) < Cl ) on the mercury surface [6] and in the order -J ) , Br ) , Cl ) < NO 3 ) < SO 2 NH 2 ) < ClO ) 4 < SO 4 2) on the solid indium electrode [6]. According to Munoz et al The addition of KCN to the solution of In(NO 3 Þ 3 Á 5H 2 O and D(+)-Glucose (Figure 3, curve 1), leads to an increase in the pH-value to 8.7 and to polarisation of the cathodic process compared with those in the initial solution ( Figure 2, curve 1).…”
Section: Effect Of Different Anions On the Electrode Processes In Thementioning
confidence: 99%
“…The influence of various anions on the cathodic reduction, as well as on the anodic ionisation, of indium has been studied on both an amalgam and a solid indium electrode in different acid electrolytes (sulphate, chloride, etc.) [4][5][6]. However, the possible effect of the type of indium salts (nitrate, sulphate and chloride) on the properties of the alkaline indium electrolytes was also not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Depositing a thin layer of indium on the surface of the negative zinc plate and current collector suppresses self-discharge of the batteries. The electrochemical behavior of indium in acidic and weak alkaline solutions has been widely reported [18][19][20][21][22][23][24], but is less well understood in an alkaline solution [25][26][27][28] such as the electrolyte for a zinc-air high-energy battery.…”
Section: Introductionmentioning
confidence: 99%